Evaluation of renewable hybrid barriers in terms of carbon emission with concrete and steel barriers - Birinci, Emre; Yorur, Huseyin; Yumrutas, H. Ibrahim; Duyar, Ahmet (AVES YAYINCILIK A.Ş., 2021)
Roadside barriers called as passive safety systems are presently produced from various materials such as steel, concrete, wood, and plastic. Existing roadside barriers have prioritized safety over aesthetics and environmental concerns. To this end, a new environmental barrier-the renewable hybrid barrier (RHB)-has been designed that can fulfill safety requirements as well as add value in terms of aesthetics. Sand is placed inside the barrier, and the barrier's outer shell is covered by fir timber. A life cycle analysis was completed to ensure the sustainable production of RHBsand to better understand their environmental impacts. The amount of greenhouse gas emitted into nature during the production of RHB and steel and concrete barriers was calculated and compared. Our results showed that concrete and steel barrier production releases approximately 4.5 times more greenhouse gases than RHB production. The live biomass equivalent of the wood materials used in RHB production was also calculated. We found that RHBs sequestrated 45.94 kg-CO(2)eq. It is thought that more widespread use of RHBs can contribute positively to the environment and nature.
Keywords: Forestry; SD1-669.5; 13. Climate action; 11. Sustainability; 7. Clean energy; 12. Responsible consumption